Public-Speaking Contest In BM - Sunday Star, (2008)
UNIVERSITI Putra Malaysia (UPM) together with the Information and Higher Education ministries will be organising Peniti V 2008 a public speaking competition in Bahasa Malaysia on Feb 16 and 17.